PROFITABILITY RATIO ANALYSIS TO ASSESS FINANCIAL PERFORMANCE AT BANK SYARIAH INDONESIA (BSI) - Ramadhani, Khusnul Khatimah Putri; Haeruddin, M. Ikhwan Maulana; Nurman; Amin, Andi Mustika; Aslam, Annisa Paramaswary (Journal Management & Economics Review (JUMPER), 2023)
This research aims to find out and analyze the financial performance of Bank Syariah Indonesia for the 2021-2022 quarter period, ratios based on profitability, namely net profit margin, return on assets, return on equity, and operational expenses to operating income. This research uses a quantitative approach using profitability ratio measurements. The data studied is in the form of Bank Syariah Indonesia's financial reports for the quarterly period 2021-2022. Based on the results of the analysis, it was concluded that the performance based on Net Profit Margin (NPM) was in very good criteria, the Return On Assets (ROA) was in fairly good criteria, the Return On Equity (ROE) was in fairly good criteria, and the Operational Expenses on Operational Costs (BOPO) are in perfect criteria.